2007
DOI: 10.1271/bbb.70409
|View full text |Cite
|
Sign up to set email alerts
|

A Protein Kinase C-Encoding Gene,pkcA, Is Essential to the Viability of the Filamentous FungusAspergillus nidulans

Abstract: A protein kinase C (PKC)-encoding gene (pkcA) was isolated from the filamentous fungus Aspergillus nidulans. Although we attempted to isolate pkcA deletion mutants, we obtained only heterokaryons that had both DeltapkcA and pkcA(+) nuclei. Conidia produced by the heterokaryon germinated. The germ tubes, however, lysed frequently and no colony formation was observed, indicating that the pkcA gene is essential to the viability of A. nidulans. We constructed conditional mutants (alcA(p)-pkcA mutants) that express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 46 publications
4
38
0
2
Order By: Relevance
“…It has been described that if an essential gene is deleted, rather than causing death, the null allele will be rescued by spontaneous generation of a heterokaryon (34). An example had been described for the filamentous fungus Aspergillus nidulans, in which the deletion of the protein kinase C-encoding gene (pkcA) was lethal and only heterokaryotic strains were obtained (18).…”
Section: Discussionmentioning
confidence: 99%
“…It has been described that if an essential gene is deleted, rather than causing death, the null allele will be rescued by spontaneous generation of a heterokaryon (34). An example had been described for the filamentous fungus Aspergillus nidulans, in which the deletion of the protein kinase C-encoding gene (pkcA) was lethal and only heterokaryotic strains were obtained (18).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest the involvement of protein kinase C (PkcA), but direct proof that places PkcA in line with the MAP kinase module in Aspergillus spp. is still lacking (10)(11)(12). Kwon and colleagues recently characterized five of six Rho GTPases of Aspergillus niger, and beside other functional aspects, they found that Rho2 and Rho4 are important to withstand stress caused by chitin binding agents (13).…”
mentioning
confidence: 99%
“…In A. nidulans, the Rho family GTPase RhoA was shown to be involved in establishing polarity, branching, and cell wall synthesis (13). It was suggested that the protein kinase C (PKC)-encoding gene pkcA plays an essential role in the maintenance of cell integrity and polarized growth in A. nidulans (18,41,46). The A. nidulans MpkA protein is involved in germination of conidial spores and polarized growth (4), and transcription of the mpkA gene seems to be autoregulated by the CWI pathway via MpkA (8).…”
mentioning
confidence: 99%